PENGARUH PENGUASAAN DIKSI TERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI OLEH SISWA KELAS XI SMA NEGERI 1 SIABU - Mannah, Nur (Linguistik : Jurnal Bahasa dan Sastra, 2023)
The purpose of this study was to determine the mastery of diction, the ability to write explanatory texts and the influence of diction mastery on the ability of explanatory texts of grade XI students of SMA Negeri 1 Siabu for the 2022-2023 academic year. The type of research used is quantitative with experimental design. The sampling technique was carried out randomly (random sampling) so that class XI IPA-3 was obtained as a research sample with a total of 31 students. The research Instrumens used are tests consisting of multiple choice to measure mastery of diction and essay tests to measure students' ability to write explanatory texts. Hypothesis testing is carried out through the "r" product moment correlation technique with the help of the SPSS Statistic program version 26. The results showed that the mastery of diction and explanatory text skills of grade XI students of SMA Negeri 1 Siabu for the 2022-2023 school year were still lacking with average scores of 45.48 and 40.16, respectively. The correlation test results show the value of r = 0.412 (medium) and the value of sig. 0.02 0.05 so that the hypothesis is acceptable. The conclusion is that there is a significant influence of mastery of diction on the ability to write explanatory texts for grade XI students of SMA Negeri 1 Siabu for the 2022-2023 school year.